ETHNIC GROUPS AND SETTLEMENT PATTERN IN KELURAHAN KESAWAN MEDAN CITY - Saragi, Alexander Adrian (Talenta Publisher, 2021)
Kesawan sub-district is one of the sub-district that has many roles in the history of Medan. Initially, the Kesawan sub-district was a Malay sub-district in 1880, and then since the Dutch colonial era, ethnic Chinese began to enter the Kesawan sub-district along with compensation for the expiration of Chinese employment contracts as workers at deli tobacco plantations owned by the Dutch government. Over time, the Kesawan sub-district was sought by ethnic Chinese as a trading area to develop into Chinatown. Currently, the Kesawan sub-district has various ethnicities scattered in each sub-district area. Ethnic groups consist of groups whose members each identify themselves with the other by creating parameters. Ethnically diverse communities tend to group themselves, creating patterns of settlements. In some studies, it was found that kinship factors can be the determining factor in the formation of settlements closely related to social ties, cultural and religious rules, and economic activities. Based on this fact, it can be said that each ethnic group can influence the location of its residents and the principles it adheres to. Patterns of settlements created from ethnic groups can identify specific identities that are more highlighted so as to have differences with other settlements. The results of the study found that most of the settlement patterns of the Kesawan sub-district are influenced by ethnic Chinese who mostly work in the trade sector, while ethnic Tamils are also seen on the outskirts of the Kesawan sub-district. Â